2014
DOI: 10.1002/cncr.28911
|View full text |Cite
|
Sign up to set email alerts
|

A validated miRNA profile predicts response to therapy in esophageal adenocarcinoma

Abstract: BACKGROUNDIn the current study we present a validated miRNA signature to predict pathologic complete response (pCR) to neoadjuvant chemoradiation in esophageal adenocarcinoma.METHODSThree patient cohorts (discovery, n = 10; model, n = 43; and validation, n = 65) with locally advanced esophageal adenocarcinoma were analyzed. In the discovery cohort 754 miRNAs were examined in pretreatment tumor biopsy specimens using a TaqMan array. Of these, the 44 most significantly altered between tumors with pCR and non-pCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 30 publications
1
60
0
Order By: Relevance
“…Mounting evidence suggests that miRNA profiles may be more efficient than gene profiles in discriminating different disease states and diseased versus nondiseased states (9,10). A role for miRNAs has been implicated in the pathogenesis of EAC, with several potential diagnostic and prognostic miRNA markers identified (11,12). We have previously demonstrated that both miR-31 (13) and miR-330-5p (14) are significantly decreased in pretreatment tumor biopsies from esophageal cancer patients who subsequently have a poor response to neoadjuvant CRT, highlighting a potential role for these miRNAs in the tumor response to CRT.…”
Section: Tissue Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mounting evidence suggests that miRNA profiles may be more efficient than gene profiles in discriminating different disease states and diseased versus nondiseased states (9,10). A role for miRNAs has been implicated in the pathogenesis of EAC, with several potential diagnostic and prognostic miRNA markers identified (11,12). We have previously demonstrated that both miR-31 (13) and miR-330-5p (14) are significantly decreased in pretreatment tumor biopsies from esophageal cancer patients who subsequently have a poor response to neoadjuvant CRT, highlighting a potential role for these miRNAs in the tumor response to CRT.…”
Section: Tissue Collectionmentioning
confidence: 99%
“…These data support miR-187-mediated regulation of these gene targets in EAC cells. Given the decreased expression of miR-187 in EAC tumors from poor responders, this suggests that the genes and/or pathways downregulated by miR-187 are likely to demonstrated that dysregulation of four miRNAs (miR-505*, miR-99b, miR-451 and miR-145*) was significantly associated with a pCR (12). Three miRNAs (miR-145*, miR-886-5p and miR-720) that we identified as being altered between responders and nonresponders in this study were also highlighted by Skinner and colleagues in pCR versus non-pCR patients.…”
Section: Mir-187 Modulates Radiosensitivity and Chemosensitivity In Ementioning
confidence: 99%
“…In this context recent studies have shown promising markers such as stem cell markers in oesophageal cancer [44] and microRNAs as predictive biomarkers for response [45]. These findings have not yet been validated and their clinical relevance needs to be further elucidated.…”
Section: Characteristicmentioning
confidence: 99%
“…miRNAs regulate gene expression at the post-transcriptional level by binding to the 3'-UTR of their target mRNAs (13). A number of studies have demonstrated that miRNA expression is associated with cell proliferation, metastasis, invasion and and response to therapy (14)(15)(16)(17)(18)(19)(20). miRNA expression differs between cancer tissues and adjacent normal tissues in patients (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%